Pachydermoperiostosis mimicking acromegaly: A case report (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Pachydermoperiostosis (PDP) is a rare clinical condition that is characterized by pachyderma (thickened facial skin), skeletal changes (periostosis), excessive sweating (hyperhidrosis), and acropachia (digital clubbing). Making a diagnosis followed by a proper care plan can be extremely challenging even for experienced clinicians due to the rarity of this disease. It mimics the clinical and radiographic manifestations of acromegaly. Acral enlargement, cutis verticis gyrate, facial coarsening, hyperhidrosis, seborrhea, and acne are common in pachydermoperiostosis as well as in acromegaly. Therefore, it should be considered one of the differential diagnoses in evaluating acromegalic patients. In this case report, we discuss a 22-year-old man with progressive enlargement of his hands and feet along with sweating but there was no biochemical evidence of acromegaly and was finally diagnosed as a case of pachydermoperiostosis.J Assoc Clin Endocrinol Diabetol Bangladesh, July 2023; 2 (2): 71-74